Alone With Goffman: Impression Management and the TV Series - Beames, Simon; Andkjær, Søren; Radmann, Aage (Frontiers in Communication, 2021)
Alone is an American reality television series on the History Channel. The show features 10 contestants who are vying to outlast each other, while living off the land. Notably, there is no camera crew and contestants must film themselves everyday; the production team creates a weekly program that marks the journeys of each individual. This study sought to understand the degree to which participants are able to shape their public identities through the video footage they shot and was subsequently edited in Alone’s cutting room. The research team employed an explorative case study methodology, which allowed them to watch hours of publicly available official video clips from the History Channel’s Alone Youtube channel. The analysis was driven by theory (Goffman’s Presentation of self conceptual framework) and an inductive thematic analysis, which took place in a cyclical fashion through interpretation meetings at the end of each of the six series that were watched. Findings first showed that contestants were performing to multiple audiences, such their families, the public, the producers, and even God. Second, the boundary between the front stage and backstage was highly blurred. Third, contestants were able to continue shaping and ‘repairing’ their identities through their own social media outlets after the program. Finally, the theme of gendered approaches to living outdoors shone through in ways that were very complex, overlapping and non-binary. There is an undeniably strong ‘impression management tension’ between the selves that participants wanted to project and the narratives that were constructed by the Alone program’s producers.